Re‐meander, rewet, rewild! Overwhelming public support for restoration of small rivers in the three Baltic Sea basin countries. Issue 5 (17th February 2022) - Giergiczny, Marek; Valasiuk, Sviataslau; Kotowski, Wiktor; Galera, Halina; Jacobsen, Jette B.; Sagebiel, Julian; Wichtmann, Wendelin; Jabłońska, Ewa
Abstract : Baltic Sea is one of the World's most oxygen‐depletes seas, so the region requires urgent mitigation measures to significantly reduce nitrogen and phosphorus inputs from land through rivers, which cannot be achieved without large‐scale restoration of wetland buffer zones. The manuscript summarizes the findings of the discrete choice experiment aimed at assessment of the preferences of Danish, German, and Polish citizens toward ecosystem services of lowland small rivers of the Baltic Sea basin. Our results suggest that respondents in all the studied countries are willing to pay substantial amounts to improve water quality in rivers and the Baltic Sea, as well as to restore naturally meandering rivers and natural riparian vegetation. Wild marshes and Wetland agriculture were equally valued as the most desirable options. Respondents systematically cared about the appearance of small rivers in their neighborhood. We conclude that re‐meandering, rewetting of floodplains, and restoration of wild marshes (i.e. natural wetland vegetation) or development of wetland agriculture could gain a lot of public support in Europe.